2019
DOI: 10.1371/journal.pone.0209602
|View full text |Cite
|
Sign up to set email alerts
|

Contextual influences on the choice of long-acting reversible and permanent contraception in Ethiopia: A multilevel analysis

Abstract: BackgroundLong acting reversible and permanent contraception (LARPs) offer promising opportunities for addressing the high and growing unmet need for modern contraception and helps to reduce unintended pregnancies and abortion rates in sub-Saharan Africa (SSA). This study examines the contextual factors that influence the use of long acting reversible and permanent contraception among married and fecund women in Ethiopia.MethodWe use data from the 2016 Ethiopian Demographic and Health Survey to examine the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 25 publications
2
41
1
Order By: Relevance
“…Our finding of injectables (short-acting method) as the predominant method of use (65% in 2018) is in line with findings in many Sub-Saharan countries including Ethiopia, where in 2016 injectables accounted for 64% of the method use [35]. Nevertheless, long-acting method users (IUDs, implant, sterilization) were identified as significantly more likely to receive good counseling.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our finding of injectables (short-acting method) as the predominant method of use (65% in 2018) is in line with findings in many Sub-Saharan countries including Ethiopia, where in 2016 injectables accounted for 64% of the method use [35]. Nevertheless, long-acting method users (IUDs, implant, sterilization) were identified as significantly more likely to receive good counseling.…”
Section: Discussionsupporting
confidence: 87%
“…In Ethiopia, the public sector plays a major role in the provision of family planning services and study on the technical quality of family planning counseling reported higher quality in public facilities when compared to the private sector [35,20]. Our results indicated that women whose contraception source was the public sector had higher odds of receiving good counseling.…”
Section: Discussionmentioning
confidence: 62%
“…Maternal Mortality Rate in 2016 was 412 /100,000 live births and under 5 child mortality was 67/1000 live births [2]. From 2000 to 2016, lower fertility rates and increased family planning utilization was documented in Ethiopia [2][3][4]. The total fertility rate was reduced from 5.5 in 2000 to 4.6 in 2016 with significant regional variability.…”
Section: Introductionmentioning
confidence: 99%
“…Ethiopia is the second most populous and tenth biggest country in Africa [1]. According to the 2016 Ethiopian Demographic and Health Survey (EDHS), the estimated total population is 102 million, with 80.2% living in rural parts [2]. Maternal Mortality Rate in 2016 was 412 /100,000 live births and under 5 child mortality was 67/1000 live births [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation